On The Issue of the Categorization of Administrative Offences - V. I. Surgutskov (Сибирское юридическое обозрение, 2019)
Some problems of modern administrative-tort and criminal legislation and law are considered. On the positive side, the sequence of the legislator is assessed regarding the delimitation of the norms of criminal and administrative responsibility. Attention is focused on the heterogeneity of administrative offenses due to the presence of various bodies of administrative jurisdiction, the establishment of different statutes of limitations, the existence of a comprehensive system of administrative penalties. The necessity of categorizing administrative offenses, the purpose of which is to differentiate administrative responsibility, is noted. The main criterion for highlighting gross administrative offenses has been named, which should be a strict form and (or) a large amount of sanctions applied. It is concluded that any gross administrative offense should be considered a socially dangerous administrative offense. The significance of the official legalization of the concepts of gross (socially dangerous) administrative offense and criminal misconduct is revealed.